Impact assessment of biodiesel production using CaO catalyst obtained from two different sources. Issue 1 (1st January 2019) - Ayoola, A.A.; Fayomi, O.S.I.; Adeeyo, O.A.; Omodara, J.O.; Adegbite, O.
Abstract: In this research work, the comparative analysis of the production of high yield and environmental friendly biodiesel obtained from the transesterification of waste soybean oil, using technical grade CaO catalyst and CaO catalyst derived from chicken eggshells, was investigated. The results of the transesterification process, SEM (using ME 600T polarising optical microscope) and XRF (using Thermo Scientific ARL OP-TIM'X 166) analysis revealed a similar catalytic performance trend when the two forms of the CaO catalysts were used separately. For technical grade CaO catalyst (using response optimizer), the optimal conditions established for the production of biodiesel were methanol/oil mole ratio of 7.1, catalyst concentration of 5.9 wt/wt% oil and reaction time of 2.1 hours, with 92.6% biodiesel yield. Using CaO catalyst derived from chicken eggshells, the optimal conditions were 7.0 methanol/oil mole ratio, 6.0 wt/wt% catalyst concentration and reaction time of 2.2 hours, with 91.4% biodiesel yield. Impact assessment of the biodiesel production was carried out using ReCiPe Endpoint (E) V1.12/World ReCiPe E/E method (SimaPro 8.0 software) and AAnalyst 200 Perkin Elmer (AAS). The results of the impact assessment showed that technical grade CaO catalyst has more negative impact on human health and a lesser impact on ecosystems. In contrast, CaO catalyst derived from chicken eggshells waste has a fairly lesser negative impact on human health and a fairly more pronounced negative effects on ecosystems.